Penanda Klausa Adverbial Dalam Bahasa Angkola - Melani Rahmi Siagian; Mulyadi Mulyadi (Balai Bahasa Sumatera Utara, 2021)
An adverbial clause is a subordinate clause that serves to provide information on the main clause. The presence of an adverbial clause is not a must, but it can help create coherence in a discourse. This study aims to describe the markers of adverbial clauses in Angkola language. The method used is descriptive qualitative markers. Data collections are conducted by speaking, listening, and taking notes. The data in this study are adverbial clauses in Angkola language obtained from native Angkola speakers and also written sources obtained from Angkola language books. Data analysis was carried out by matching the data with the theory contained in the study, namely adverbial clause markers in Angkola language sentences. The results showed that there were five types of adverbial clauses in Angkola language, namely temporal clauses marked by the word dung 'after' and dompak 'when', conditional clauses marked by the word molo 'if', causal clauses (causal clause) which is marked by the word harana 'because', the purpose clause (purposal clause) which is marked by the word anso 'so that/so', and the concession clause (consessive clause) which is marked by the words bope 'although' and aha pe 'what ever'. The use of adverbial clauses can be found at the initial or final position in a sentence.